DETERMINATION OF ELIGIBILITY FOR RECEIVING THE FAMILY HOPE PROGRAM ASSISTANCE USING THE EVALUATION BASED ON DISTANCE FROM AVERAGE SOLUTION (EDAS) METHOD - Br Pohan, Dian Cinta Hasmi; Husein, Ismail; Sari, Rina Filia (Pena Cendekia Insani, 2025)
This study proposes a decision support framework for determining eligibility for Indonesia’s Program Keluarga Harapan (PKH) using the Evaluation Based on Distance from Average Solution (EDAS) method. Seven criteria derived from national social welfare policy were weighted using the Analytic Hierarchy Process (AHP), achieving a consistency ratio of 0.038. The model was applied to 98 household alternatives in Air Merah Village. The resulting assessment scores ranged from 0.0119to 0.7866. A Monte Carlo sensitivity analysis with 5,000 iterations under ±10% ±15% weight perturbations yielded a high Spearman rank correlation (rho = 0.91,95% CI [0.89, 0.93]), indicating strong ranking stability. The EDAS results showed 78% agreement with manual village selection and 80% alignment within the top-20 priority group. The proposed framework reduces subjectivity and improves transparency in beneficiary selection. Limitations include the cross-sectional design and single-location data. The model is scalable and suitable for broader policy implementation.